Pendekatan Konstruktivisme Dalam Pembelajaran Sejarah Lokal - Juliandry Kurniawan Junaidi (Bakaba, 2018)
This article tries to give input regarding innovation in history learning, especially in the aspect of the learning approach. Learning history is often regarded as a boring subject, full lessons with memorizing facts as well as the way the teaching is sometimes still using the old paradigm, where learning activities are teacher-centered, students only become passive subjects. To overcome this problem so that teaching history becomes more interesting and meaningful, it is necessary to find alternative solutions. The solution offered in this article is to use a constructivism approach, by applying this approach it is expected that students are able to build their knowledge independently so that they are able to capture the meaningfulness of a historical event. Especially local history which has been facilitated since the curriculum changes, because so far local history has not been seriously explored in historical teaching materials in schools.